Childhood Hypercalciuric Hypercalcemia With Elevated Vitamin D and Suppressed Parathyroid Hormone: Long-Term Follow Up - Gurevich, Evgenia; Levi, Shelly; Borovitz, Yael; Alfandary, Hadas; Ganon, Liat; Dinour, Dganit; Davidovits, Miriam (Frontiers in Pediatrics, 2021)
Purpose: Hypercalcemia with low parathyroid hormone (PTH) level, hypercalciuria, nephrocalcinosis, or nephrolithiasis, was recently reported as caused by mutations in CYP24A1 and SLC34A genes. These encode for vitamin D-24A-hydroxylase and for the renal phosphate transporters NaPiIIa and NaPiIIc, respectively. We aimed to describe the clinical course of these monogenic disorders in patients with and without found mutations during long-term follow-up. Methods: Ten patients with hypercalcemia, hypercalciuria, elevated 1,25-(OH)2D levels and suppressed PTH were followed in our center during 1998-2019. Relevant laboratory and imaging data and results of genetic evaluation were retrieved from medical files. Results: The median age at presentation was 9.5 months (range 1 month-11 years), six were males, and the median follow-up time was 3.8 (1.1-14) years. Mutations in CYP24A1 and SLC34A3 were identified in three and one patients, respectively. Five patients presented with nephrocalcinosis, three with nephrolithiasis, and two had normal renal ultrasound. High blood calcium and 1,25-(OH)2D levels at presentation decreased during follow-up (11.1±1 vs 9.9±0.5 mg\dl (p=0.012), and 307±130 vs 209±65 pmolł (p=0.03), respectively); this paralleled an increase in suppressed PTH levels (5.8±0.9 vs 11.8±7.3 pg\ml, p=0.2). Substantial improvements in hypercalciuria and renal sonography findings were not observed. Two patients had impaired renal function (eGFR 84-88 ml\min\1/73m2) at the last follow up. Interventions included appropriate diet, citrate supplementation, and thiazides. Conclusion: Despite improvement in hypercalcemia and 1,25-(OH)2D levels, not all the patients showed improvements in hypercalciuria and nephrocalcinosis. Deterioration of renal function was also observed. Long-term follow up and intervention to prevent nephrocalcinosis and nephrolithiasis are recommended in these children.